2004
DOI: 10.1200/jco.2004.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Mammaglobin Is Associated With Low-Grade, Steroid Receptor-Positive Breast Tumors From Postmenopausal Patients, and Has Independent Prognostic Value for Relapse-Free Survival Time

Abstract: These results demonstrate that the assessment of the tumor mRNA expression level of the breast-specific protein mammaglobin could be useful to stratify patients for individual adjuvant treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 18 publications
5
59
0
1
Order By: Relevance
“…Indeed, MGB1 has steroid-responsive elements in its promoter region, 1 and recent analysis based on mRNA expression also revealed an association of MGB1 with ER expression. 26,27 In conclusion, MGB1 is a highly specific marker of breast cancers, and its expression was detected in about half the breast cancers examined. The expression of MGB1 was correlated with that of ER, but was unaffected by other clinicopathological features, including pathological stage, HER2 gene status and disease-free survival rate.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, MGB1 has steroid-responsive elements in its promoter region, 1 and recent analysis based on mRNA expression also revealed an association of MGB1 with ER expression. 26,27 In conclusion, MGB1 is a highly specific marker of breast cancers, and its expression was detected in about half the breast cancers examined. The expression of MGB1 was correlated with that of ER, but was unaffected by other clinicopathological features, including pathological stage, HER2 gene status and disease-free survival rate.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that mammaglobin mRNA levels were detectable at higher levels in breast tumors compared with normal breast tissue, and mammaglobin was not expressed at the RNA level in several normal tissues (3). Moreover, mammaglobin protein expression in breast tumors was observed at high frequency (3,15,16) independent of stage, grade, or histology (2). This evidence of breast tissue specificity has led to the application of mammaglobin as a marker for metastatic spread of breast cancer to lymph nodes (5).…”
Section: Discussionmentioning
confidence: 99%
“…19 A series of 183 patients with unilateral, resectable breast cancers who had undergone resection of their primary tumors between November 1987 and December 1997 were selected based on the availability of RNA in the Original Article tumor bank of the Department of Laboratory Medicine of the RUNMC. 20 This bank contains material from breast cancer patients of 7 different hospitals of the Comprehensive Cancer Centre East in the Netherlands. The inclusion and exclusion criteria have been described earlier.…”
Section: Patientsmentioning
confidence: 99%
“…The inclusion and exclusion criteria have been described earlier. 20 Postoperative radiotherapy was given to the breast after an incomplete resection or after breast-conserving treatment, or parasternal when the tumor was medially localized. Axillary irradiation was given in the case of positive lymph nodes.…”
Section: Patientsmentioning
confidence: 99%